Evaluation of the Obstacles against the Economic Development of Cihanbeyli Rural Area - Fadim Yavuz; Ayla Bozdað (European Regional Science Association (ERSA), 2014)
Cihanbeyli, located in Salt Lake (SL) Basin, is the largest county of Turkey in terms of its area. In total 56.105 people live in the county and its rural population is 7.005. According to data of 2011 year, Cihanbeyli's social development level is at the tenth of 31 counties of the Konya province and the county is among the least developed counties' group. SL basin is an important wetland in Turkey in terms of biodiversity conservation and international criteria. The most important economic activities in the area are agriculture, livestock and industrial salt production. All the cultivated land is reserved for dry farming and vegetable and fruit production is at negligible quantity. Lack of forested areas, existence of barren lands, insufficient water resources for the agriculture with the impact of the SL, Being one of the Turkey's low rainfall areas, transforming the domestic and industrial waste of Konya city directly to the SL's are the negative factors affecting the agriculture in the region. Depending on the threat of drought, significant productivity and quality issues are being experienced in the region's rural area. In the region agricultural production is decreasing due to drought and intense population immigration from the county's rural areas. Desertification caused by SL, furthermore aridity caused by manufacturers' improper fertilizer uses exist in agricultural areas. Range of products is limited as a result of unconscious agricultural production. Wheat, barley and sugar beet are the products commonly grown. By identifying the obstacles against the Cihanbeyli region's economy this study aims to determine sustainable strategies activate/improve agriculture as a main source of income, thereby improve economy of the region. Results are useful in i) referring agricultural activities to the areas have good physical and environmental conditions and may achieve maximum efficiency in countryside, ii) improving non-agricultural uses in the areas are unsuitable for agriculture and low efficient, iii) avoiding the construction and environmental pressures on suitable farmland.
Keywords: Q01; Q15; Q18; 330; Agricultural land suitability; sustainable economic development; Cihanbeyli; Salt Lake Basin